Вы находитесь на странице: 1из 16

,

..

2008
1 2- 1.1. .. 1.2. 1 ( ) ... 1.3. 2 ( ) 1.4. 3 ( ) .. 1.5. .. 2 2.1. .. 2.2. 4 2.3. .. 3 4 4 6 7 9 11 13 13 14 17

, . .

1. 2- . .
A( x, y )U xx + 2 B ( x, y )U xy +C ( x, y )U yy + a ( x, y )U x +b( x, y )U y + c( x, y )U = f ( x, y )

(1)

1.1. .
I. (1) B 2 AC : B 2 AC > 0 , (1) ; B 2 AC < 0 , (1) ; B 2 AC = 0 , (1) . (1) , , D, , , . (1) () . , yU xx +U yy = 0 ( x, y ), y > 0 ; ( x,0) ; ( x, y ), y < 0 . II. , : 1. A( x, y ), B ( x, y ), C ( x, y ) ; 2. B 2 AC ; 3. (1) ( B 2 AC ); 4. : A( x, y ) dy 2 2 B ( x, y ) dxdy +C ( x, y ) dx 2 = 0 ; (2) 5. (2). : ) (2) dy:
dy = B ( x, y ) B 2 AC dx ; A( x, y )

(3)

) (3) ( (1)):

( x, y ) = C1 , 1 1 ( x, y ) = C 2 ,

(4) ; 2 ( x, y ) = C , (5) ;
4

3 ( x, y ) i 3 ( x, y ) = C ,

(6) . 6. () : (4) (3), .. (5) (3), .. = 2 ( x, y ) , , 2 , 2 ( x, y ) , .. = 2 ( x, y ) ; (6) (3):

= ( x, y ), 1 =1 ( x, y );

= Re (3 ( x, y ) + i 3 ( x, y ) ) = 3 ( x, y ), = Im(3 ( x, y ) + i 3 ( x, y ) ) = 3 ( x, y ).

7. , (1),

:
U x = U x + U x ,
2

U ( ( x, y );( x, y ) )

U y = U y + U y ,
2

U xx = U ( x ) + 2U x x + U ( x ) + U xx + U xx
2

U yy = U ( y ) + 2U y y + U ( y )

U xy = U x y + U ( x y + y x ) + U x y + U xy + U xy .

, + U yy + U yy ,

(7)

8. (1)

. (1) : :
U + F1 (U , U , U , ,) = 0 ;

:
U + F1 (U , U , U , , ) = 0 ;

:
U + U + F1 (U , U , U , , ) = 0 .

1.2. 1.
U xx 4U xy 21U yy + 2U x 3U y + 5U = x 2

(8)

. :
1. A( x, y ), B ( x, y ), C ( x, y ) :

=1, = -2, =-21. 2. B AC : B 2 AC = 4 + 21 = 25 . 2 3. B AC = 25 > 0 XOY. 4. : dy 2 + 4dxdy 21 dx 2 = 0 . (9) 5. (9). : ) (9) dy:
2

dy =

(10) ) (10) ( (9)):


y = 7 x + C1 , y + 7 x = C1 , y = 3 x + C2 , y 3 x = C2 .

dy = 7dx ,

2 25 dx ; 1 dy = ( 2 5) dx ;

dy =3dx ,

6. :

= y +7 x, = y 3 x.

7. , .
x = 7, y =1, xx = 0, xy = 0, yy = 0, x = 3, y =1, xx = 0, xy = 0, yy = 0.

(7), :
2 U x = 7U 3U , 3 U y = U + U , 1 U xx = 49U 42U + 9U, 1 U xy = 7U + 4U 3U, 21 U yy = U + 2U +U.

(8) . 8. , :
U {49 28 21} + U {42 16 42} + U {9 +12 21} + + U {14 3} + U {6 3} + 5U =

( ) 2 .
16

-100 ( U ):
U 0,11U + 0,09U 0,05U =

( ) 2 .
1600

. (8) XOY.
U 0,11U + 0,09U 0,05U =

( ) 2 ,
1600

= y + 7 x, = y 3 x.

1.3. 2.
25U xx 10U xy +U yy +U y + 2U = 5 y + 2 x

(11)

. :
1. A( x, y ), B ( x, y ), C ( x, y ) .

: =25, = -5, =1. 2. B AC : B 2 AC = 25 25 = 0 . 2 3. B AC = 0 XOY. 4. : 25 dy 2 +10 dxdy + dx 2 = 0 . (12) 5. (12). : ) (9) dy. : (5dy + dx ) 2 = 0 ; 5dy = ; dx (13) ) (13). ( ):
2

6. : () , , , = x; 7. , .
x = 1, y = 5, xx = 0, xy = 0, yy = 0, x = 1, y = 0, xx = 0, xy = 0, yy = 0.
= 5 y + x,

5 y = x + C , 5 y + x = C.

(7), :
0 U x =U + U , 1 U y = 5U , 25 U xx =U + 2U + U , 10 U xy = 5U + 5U , 1 U yy = 25U .

(11) . 8. , :
U {25 50 + 25} +U {50 50} +U{25} + +U {5} + 2U = +.

, (11) . 25 ( U ):
U + 0,2U + 0,08U = 0,4( +).

. (11) XOY.
U + 0,2U + 0,08U = 0,4( +).

= 5 y + x, = x.

1.4. 3.
U xx + 4U yy + U x 3U y + U = x 2

(14)

. :
1. A( x, y ), B ( x, y ), C ( x, y ) :

=1, = 0, =4. 2. B AC : B 2 AC = 0 4 = 4 . 2 3. B AC = 4 < 0 XOY. 4. : dy 2 + 4dx 2 = 0 . (15) 5. (15). : ) (15) dy: dy = idx ; 2 (16)
2

) (16) - . - . ( )
y = 2 xi + C , y 2 xi = C.

(17)

6. (17):
= Re( y + 2 xi ) = y , = Im( y + 2 xi ) = 2 x.

7. , .
x = 0, y = 1, xx = 0, xy = 0, yy = 0, x = 2, y = 0, xx = 0, xy = 0, yy = 0.

(7), :

1 U x = 2U , 3 U y = U , 1 U x x = 4U , 4 U y y = U
(14) . 8. , :
U {4} +U {4} +

U +U 0,75U + 0,5U + 0,25U = .

+U {3} +U {2} +U = . ( U U ):

. (14) XOY.
U +U 0,75U + 0,5U + 0,25U = .

= y, = 2 x.

1.5. . 1. . 1.1. 1.2. 1.3. 1.4. 1.5 1.6 1.7 1.8 1.9 1.1 0
U xx 8U xy 9U yy + 21U x + 3U y U = 0 . 3U xx 4U xy +U x 3U y +U = 0 . 2U xx 4U xy 6U yy U x + 7U y + 3U = 0 . 7U xy 21U yy + 2U x U y + 4U = 0 .

U xx 2U xy 8U yy + 3U y U = 0 . U xx U xy 6U yy + 2U x U = x .

U xx 16U yy +U x + 3U y 6U = 0 .

4U xx 2U xy 6U yy + 8U x +U y U = y .

U xx 8U xy + 2U x U y 5U = x + y .

6U xx U xy U yy +U x +U y U = 0 .

2. . 2.1. 2.2. 2.3. 2.4. 2.5. 2.6. 2.7. 2.8. 2.9. 2.10 .
U xx 4U xy + 4U yy + 2U x U y +U = x

2U xx 4U xy + 2U yy +U x 3U y +U = y 2 U xx 2U xy +U yy +U x 3U y + 5U = 0 3U xx 6U xy + 3U yy + 5U x 3U y + 2U = y x 4U xx 4U xy +U yy +U x 2U y +U = 0 U xx 4U xy + 4U yy U y +U = x + y 9U xx 6U xy + U yy + 7U x 2U y U = 0 2U xx 8U xy + 8U yy +U x U y +U = 0 U xx 6U xy + 9U yy + 5U x +U y 3U = y 9U xx 12U xy + 4U yy 3U x 2U y +U = 0

10

3. . 3.1. 3.2. 3.3. 3.4. 3.5. 3.6. 3.7. 3.8. 3.9. 3.10 .
U xx 2U xy 5U yy + 2U x 3U y + 5U = 0 U xx 2U xy + 10U yy + U x + 3U y 5U = 0 2U xx + 4U xy +10U yy + 8U x 3U y +U = sin x U xx 4U xy +13U yy + 7U x + 6U y = 0

2U xx + 6U xy + 8U yy + U x + 5U y 2U = y
3U xx 8U xy + 7U yy + 3U x U y + 2U = 0

3x 2

2x 3 U xx 6U xy +13U yy + 3U x U y + 4U = 0 13U xx 4U xy +U yy + 3U x + 6U y U = 0 10U xx + 2U xy +U yy +U x + 3U y = 0 3U xx + 8U xy + 6U yy + 3U x + U y 2 =

11

2. 2. 1.
A( x, y )U xx + 2 B ( x, y )U xy +C ( x, y )U yy + + a ( x, y )U x +b( x, y )U y +c ( x, y )U = f ( x, y )

(1)

. (1) :
U + a1U + b1U + c1U = f1 (,) ;

(11) (12)

:
U + a 2U + b2U + c 2U = f 2 (,) ;

: (13) , V (,) - . , , , . , ~ ~ U +c U = f (,) ; ~ ~ U + a U = f (,) ; ~ ~ U +U + c U = f (,) . (14) (11), (12), (13), ,


1 1 2 2 3 3

U +U + a3U + b3U + c3U = f 3 (,) .

U (,) = e +V (,) , , , - ,

(14)

U (,) = e +V (,), U = e + (V +V ), U = e + ( V +V ),

U = e + (2V + 2V +V ), U = e + ( + V + V +V ), V U = e + ( 2V + 2 V +V ).

(15)

12

, .. (11). , , (15).
1 b1 1 U ( , ) = e + ( , ), V a1 U = e + (V + V ), U = e + ( V + V ), U = e + ( + V + V + V ) V

(11). , e +{V +V (a1 + ) +V (b1 + ) +V (a1 + b1 + + c1 )} = f1 (,) . (16) V V


a1 + = 0, b1 + = 0.

(16)

= a1 , = b1 . (16) e + , ~ ~ U +c U = f (,) , ~ ~ c1 = 2a1b1 + a1b1 + c1 , f1 ( ,) = f1e b a .


1 1
1 1

2.2. 4
U xx 4U xy + 5U yy 3U x + U y + U = 0

(17)

. :
9. A( x, y ), B ( x, y ), C ( x, y ) :

=1, = -2, =5. 10. B AC : B 2 AC = 4 5 = 1 . 2 11. B AC = 1 < 0 XOY. 12. : dy 2 + 4dxdy + 5dx 2 = 0 . (18) 5. (18). : ) (18) dy:
2

dy =

2 1 dx ; 1 dy = ( 2 i ) dx ;

(19)

) (19) ( (17)):
13

y = ( 2 i ) x + C , y + 2 x xi = C ,

6. :

= y + 2 x, = x.

13. , .
x = 2, y = 1, xx = 0, xy = 0, yy = 0, x = 1, y = 0, xx = 0, xy = 0, yy = 0.

(7), :
3 U x = 2U + U , 1 U y =U , 1 U xx = 4U + 4U + U , 4 U xy = 2U + U , 5 U yy = U .

(17) . 14. , :
U {4 8 + 5} +U {4 4} +U {1} + +U {6 +1} +U {3} +U = 0.

U + U 5U 3U + U = 0.

(20)

(14)
U (,) = e +V (,)

. , (20), (15).
1 5 3 1 1 U ( , ) = e + ( , ), V U = e + (V + V ), U = e + ( V + V ), U = e + (2V + 2V + V ), U = e + ( 2V + 2V + V ).

(20). , e +{V + V + V (5 + 2) + V ( 3 + 2 ) + V (5 3 + 2 + 2 +1)} = 0 . (21) V V (21)


5 +2 =0, 3 +2 =0.

3 5 = , = . (21)

,
14

V +V

. (20) XOY.
V +V 15 V =0 , 2

15 V =0 . 2

= y + 2 x, = x,

U ( ,) = e

5 +3 2

V ( ,) .

15

2.3. 4. . 4.1. 4.2. 4.3. 4.4. 4.5. 4.6. 4.7. 4.8. 4.9. 4.10.
3U xx + 8U xy + 6U yy + 3U x + U y 2U = 0 . 3U xx 8U xy + 7U yy + 3U x U y + 2U = 0 .

U xx 4U xy + 4U yy + 4U x 9U y 3U = 0 . U xx 6U xy + 9U yy + 4U x 3U y 7U = 0 . U xx 2U xy +U yy 3U x + 2U y 5U = 0 . 8U xx 6U xy U yy U x 3U y U = 0 . 2U xx + 8U xy + 8U yy U x 2U y 5U = 0 .

2U xx + 6U xy + 8U yy +U x + 5U y 2U = 0 .

U xx + 2U xy 3U yy + 2U x + 7U y 3U = 0 .

4U xx 8U xy +U yy 2U x + 2U y 3U = 0 .

16